2020
DOI: 10.1038/s41598-020-72718-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysfunction following COVID-19, especially in severe patients

Abstract: The coronavirus disease 2019 (COVID-19) has been spreading worldwide. Severe cases quickly progressed with unfavorable outcomes. We aim to investigate the clinical features of COVID-19 and identify the risk factors associated with its progression. Data of confirmed SARS-CoV-2-infected patients and healthy participants were collected. Thirty-seven healthy people and 79 confirmed patients, which include 48 severe patients and 31 mild patients, were recruited. COVID-19 patients presented with dysregulated immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 33 publications
0
52
0
2
Order By: Relevance
“…Among others parameters, mild and severe forms of the COVID-19 are characterized by a marked decrease in the total number of peripheral blood lymphocytes including T cells, both CD4+ and CD8+, B lymphocytes and Natural Killer (NK) cell (Song et al, 2020). It is interesting to note that T cells from severe patients present an effector, activated and senescent phenotype mainly associated with CD8+ cells (Vardhana and Wolchok, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Among others parameters, mild and severe forms of the COVID-19 are characterized by a marked decrease in the total number of peripheral blood lymphocytes including T cells, both CD4+ and CD8+, B lymphocytes and Natural Killer (NK) cell (Song et al, 2020). It is interesting to note that T cells from severe patients present an effector, activated and senescent phenotype mainly associated with CD8+ cells (Vardhana and Wolchok, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that COVID-19 convalescent patients possess both CD4 + and CD8 + T cells responsive to SARS-CoV-2 antigens 3 . Furthermore, severe COVID-19 is associated with lymphopenia including loss of both CD4 + and CD8 + T cells 4 6 . However, it is not known whether lymphopenia contributes to severe COVID-19 or is an effect of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The number of NK cells in the peripheral blood of patients was decreased compared to healthy people, and even in the COVID-19 patients' group, severe cases had a further decrease in NK cell counts compared to mild cases ( Fig. 2 ) ( 23 42 43 44 45 ). The NK cell population comprises cytotoxic CD56 dim CD16 + NK cells and cytokine-producing CD56 bright CD16 − NK cells conferred with immunoregulatory functions.…”
Section: Innate Immune Cells In Humansmentioning
confidence: 89%